2011
DOI: 10.1007/s11274-011-0969-y
|View full text |Cite
|
Sign up to set email alerts
|

An extracellular serine protease produced by Vibrio vulnificus NCIMB 2137, a metalloprotease-gene negative strain isolated from a diseased eel

Abstract: Vibrio vulnificus is a ubiquitous estuarine microorganism but causes fatal systemic infections in immunocompromised humans, cultured eels or shrimps. An extracellular metalloprotease VVP/VvpE has been reported to be a potential virulence factor of the bacterium; however, a few strains isolated from a diseased eel or shrimp were recently found to produce a serine protease termed VvsA, but not VVP/VvpE. In the present study, we found that these strains had lost the 80 kb genomic region including the gene encodin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Recent studies have shown that a few V. vulnificus strains isolated from diseased eels do not produce VVP because they lack the structural gene vvpE . Interestingly, these strains have been shown to produce a serine protease termed VvsA . VvsA is an orthologue of an extracellular protease produced by V. parahaemolyticus , a causative agent of both human wound infection and gastroenteritis .…”
Section: Virulence Factors Of V Vulnificusmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that a few V. vulnificus strains isolated from diseased eels do not produce VVP because they lack the structural gene vvpE . Interestingly, these strains have been shown to produce a serine protease termed VvsA . VvsA is an orthologue of an extracellular protease produced by V. parahaemolyticus , a causative agent of both human wound infection and gastroenteritis .…”
Section: Virulence Factors Of V Vulnificusmentioning
confidence: 99%
“…The serine protease from V. parahaemolyticus has been reported to possess various toxic activities such as collagenolytic, cytotoxic, hemolytic and edema‐forming activity . Therefore, VvsA may be one of the critical virulence factors during eel vibriosis, which is characterized by external and internal edematous hemorrhages affecting the major organs .…”
Section: Virulence Factors Of V Vulnificusmentioning
confidence: 99%
“…However, database analysis revealed that only one protein (A5A1168 of V. cholerae strain MZO‐2; accession number AAWF01000039) might be an ortholog of VmtA, suggesting that VmtA is part of a minor group of serine proteases in the Vibrio species. Indeed, the extracellular proteases from V. parahaemolyticus and V. vulnificus are similar to chymotrypsin, but not to trypsin. In Vibrio species, it has been documented that the gene encoding a chymotrpsin‐like protease constitutes an operon with a downstream gene encoding a putative chaperon .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the extracellular proteases from V. parahaemolyticus and V. vulnificus are similar to chymotrypsin, but not to trypsin. In Vibrio species, it has been documented that the gene encoding a chymotrpsin‐like protease constitutes an operon with a downstream gene encoding a putative chaperon . However, we found the vmtA gene was a distinct transcriptional unit, indicating a different maturation mechanism for VmtA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation